The use of ipilimumab in patients with rheumatoid arthritis and metastatic melanoma. (9th February 2016) - Lee, B.; Wong, A.; Kee, D.; Neeson, P.; Shackleton, M.; McArthur, G.; Sandhu, S.
Abstract : This is a retrospective analysis addressing the impact of immune check-point blockers on pre-existing autoimmune diseases in patients with metastatic melanoma. Ipilimumab, an anti-CTLA-4 antibody, is the first and most well studied immune checkpoint inhibitor in melanoma, however, due to concerns about immune related adverse events, patients with pre-existing autoimmune disorders have been excluded from clinical trials. This report presents a case series examining the use of ipilimumab in patients with metastatic melanoma and rheumatoid Arthritis (RA). The use of immune-directed therapies in cancer patients with underlying autoimmune conditions is an important issue that poses an increasing clinical dilemma as immunotherapies gain prominence in the management of multiple cancers.